Monthly and annual total of moisture from 1962 to 2023 at Gobabeb, Namibia - Li, Yue; Marais, Eugene; Wang, Lixin (PANGAEA, 2025)
We compiled a six-decade-long (1962-2023) water availability (i.e., monthly and annual fog amount, monthly and annual rainfall amount, and annual Kuiseb River flooding occurrence days) at Gobabeb, Namibia.
Keywords: Fog amount; Gobabeb; rainfall amount